A practical study of the main transformations from social welfare to social development in Lesotho: Success factors, challenges and prospects. (May 2023) - Manyeli, Tšepang
Lesotho recently experienced a paradigm shift from social welfare to social development. The study was aimed at assessing achievements and challenges that resulted from the transition. A sequential mixed-methods approach was used. In the quantitative strand, a sample of 150 social workers and 300 beneficiaries was randomly selected, out of which a sample of four social workers' focus groups were purposively formed. Data were collected through questionnaires, structured interviews and focus group discussions. The community development programme serves as a means to incorporate a social development approach. The article recommends integration of the social development approach in specialised programmes.